Consumer acceptance of a selection of South African red wines : intrinsic, extrinsic and socio-demographic influences - Basson, Shantelle (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc)--Stellenbosch University, 2012.